Product market power and its implications for the Australian economy - Jonathan Hambur (The Australian Government, The Treasury, 2021)
This paper documents the evolution of firm mark-ups in the Australian economy using a large and representative database derived from administrative tax data. I find that mark-ups have increased by around 5 per cent since the mid-2000s, which is less than previously documented for Australia, and slightly less than has been documented for the average advanced economy. While part of this appears to reflect technological change, there also appears to have been an increase in market power and decline in competition over the period. This increase in market power appears to explain part of the slowdown in productivity growth observed in Australia over the past decade, as it has been associated with slower efficient reallocation of resources from low-productivity to high-productivity firms.
Keywords: C23; C55; D22; D24; D40; E24; 330; competition; productivity; firm-level; BLADE